Improving student’s virtue character through the perryso dialogue model - Hambali, IM; Khasairi, Moch.; Hanafi, Yusuf; Thoriq, Titis (Journal of Education and Learning (EduLearn), 2025)
The results of needs assessments for a number of universities show that virtuous character behavior shows a number of problems that require efforts by universities to carry out massive and planned virtuous character education movements. The perryso dialogue model based on cognitive behavior modification was developed to overcome a number of problems related to the good character of students. This guide product is suitable for use and application to students because it meets the theoretical and practical aspects of acceptance. The product has met the elements of suitability of the guide format, acceptability in terms of psychological material and suitability of the guide content with the criteria of usefulness, accuracy, convenience, attractiveness, and appropriateness. Thus, the perryso dialogue model guide based on cognitive behavior modification for developing the virtuous character of Universitas Negeri Malang (UM) students is suitable for use by lecturers. Building the virtuous character of (UM) students can provide significant changes to students' thinking processes which include critical, analogical, and association aspects. Product advantages: i) the dialogue guide is scientific, which means this guide is tested empirically through an acceptance test stage by experts and ii) this guide is complete, which means the guide contains material concepts about virtue character along with instruments to determine the success of implementing dialogue activities.